Effect of the TIM-3/Gal-9 signaling pathway on macrophage polarization in peri-implantitis - Lu-Jin Cheng; Shu-Ya Dong; Xiao-Feng Ni; Long Mei; Jun-Gang He; Aynur Mamat; Zhong-Cheng Gong (PLoS ONE, 2025)
Introduction Peri-implantitis (PI) is a common complication of oral implant surgeries. Understanding the role of T-cell immunoglobulin and mucin domain-containing protein 3 (TIM-3) and its ligand galectin-9 (Gal-9) in PI is essential for advancing treatment strategies. This study investigated the effect of the TIM-3/Gal-9 signaling pathway on macrophage polarization in PI. Methods We included 31 PI patients and 30 controls with healthy implants. Peripheral blood and peri-implant tissue samples were collected. Serum Gal-9 and cytokine levels were measured using ELISA. CD86, CD206, and TIM-3 expressions were analyzed via immunohistochemistry. Lipopolysaccharide was used to induce a PI environment in cells, which were divided into blank control, control, and Gal-9 groups. Flow cytometry detected M1, M2, TIM-3+M1, and TIM-3+M2 proportions. Results There were positive expressions of CD86 and CD206 in peri-implant tissues of PI patients, indicating the presence of both macrophage phenotypes, with a notable predominance of M1. The proportions of CD86+M1 macrophages and CD206+M2 macrophages in peripheral blood were significantly elevated in the PI group, resulting in an increased M1/M2 ratio in the PI group. Correlation analyses indicated that both M1 and M1/M2 were positively correlated with the modified plaque index, modified sulcular bleeding index, and probing depth, suggesting that the M1/M2 ratio reflects the clinical severity of PI. In vitro experiments showed that the addition of Gal-9 led to a significant increase in the proportion of TIM-3+M1 and TIM-3+M2 macrophages and a decrease in M1 cell proportions and M1/M2 ratio. The Gal-9 group exhibited significantly reduced levels of pro-inflammatory cytokines IL-1β and TNF-α. A strong negative correlation was found between TNF-α levels and TIM-3+M1 macrophages. However, no significant difference was found in the anti-inflammatory cytokine IL-10 between the control and Gal-9 groups. Conclusion The TIM-3/Gal-9 signaling pathway plays a crucial role in modulating macrophage polarization in PI. This work may provide evidence for the development of novel therapeutic targets for managing PI.